1999
DOI: 10.1007/s11743-999-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior of surfactant‐polyacrylamide mixtures with kaolin

Abstract: The adsorption behavior of three surfactantshexadecylpyridinium bromide (HPyBr), sodium dodecylbenzene sulfonate (SDBS), and Triton X-100 (TX-100)-on kaolin from aqueous solution is monitored as a function of pH. The nature and shape of the adsorption isotherms are typical and highly dependent on the surfactant structure. All three surfactants adsorb on kaolin beyond the limits of monolayer coverage. Isotherms for HPyBr fit the Langmuir equation well. SDBS isotherms are typical of a two-stage process, and TX-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The adsorption characteristics of binary or ternary surfactant systems were also previously investigated. The adsorption data of three surfactants on kaolinite indicated that the surfactant structure had a considerable effect on the adsorption isotherms and that competitive and synergistic effects occurred in the surfactant–polyacrylamide system . In addition, when the molar ratio of cationic and anionic surfactant binary systems was >1.1, the adsorption was negligible and the presence of nonionic surfactant impaired the adsorption of the ionic species .…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption characteristics of binary or ternary surfactant systems were also previously investigated. The adsorption data of three surfactants on kaolinite indicated that the surfactant structure had a considerable effect on the adsorption isotherms and that competitive and synergistic effects occurred in the surfactant–polyacrylamide system . In addition, when the molar ratio of cationic and anionic surfactant binary systems was >1.1, the adsorption was negligible and the presence of nonionic surfactant impaired the adsorption of the ionic species .…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of SDBS could reduce the interfacial tension between FH and water as well as enhance the wettability of the FH surface, promoting the external diffusion of arsenic to the FH surface (Sastry and Dave, 1999;Thibaut et al, 2000;Wang and Kwak, 1999;Yang et al, 2007Yang et al, , 2010. The nonionic surfactant Triton X-100 exerted different impacts on the adsorption kinetics of As(V) and As(III).…”
Section: Adsorption Kinetics Of Arsenic Coexisting With Sdbs or Tritomentioning
confidence: 99%
“…The nature and shape of the adsorption isotherms were typically very much dependent on the surfactant structure. All three surfactants adsorbed onto kaolin beyond the limits of a monolayer coverage (Sastry and Dave 1999).…”
Section: Introductionmentioning
confidence: 96%